Impact of night shift rotations on nursing performance and patient safety: A cross‐sectional study - Abdalkarem F. Alsharari; Fuad H. Abuadas; Mohammed N. Hakami; Adel A. Darraj; Magbool W. Hakami (Wiley, 2021)
Abstract Aim Hospitals operate on a 24‐hr basis, with shiftwork being unavoidable for most nurses. This study aims to explore the impact of night shiftwork rotations on nurses' physiological status, work performance and patient safety concerns among nurses in public hospitals. Design A descriptive predictive correlational design using a self‐administered questionnaire. Methods Electronic and printable survey questionnaires were distrusted among nurses working in public hospitals in multiple regions of Saudi Arabia. The study recruited 1,256 nurses from different nationalities, hospital work units and work experience. Results A large proportion of nurses on night shiftwork encountered patient safety issues (85.7%) and physiological consequences (93.6%). Counselling sessions and programmes to support at‐risk nurses are recommended.